IMovie HD & iDVD 5 : the missing manual - Pogue, David, 1963- (Missing manual., 2005)
The latest versions of iMovie HD and iDVD 5 are, by far, the most robust moviemaking applications available to consumers today. But whether you're a professional or an amateur moviemaker eager to take advantage of the full capabilities of these applications, don't count on Apple documentation to make the cut. You need iMovie HD & iDVD 5: The Missing Manual iMovie HD & iDVD 5: The Missing Manual Capturing quality footage (including tips on composition, lighting, and even special-event filming) Building your movie track, incorporating transitions and special effects, and adding narration, music, and sound Working with picture files and QuickTime movies Reaching your intended audience by exporting to tape, transferring iMovie to QuickTime, burning QuickTime-Movie CDs, and putting movies on the Web (and even on your cell phone!) Using iDVD 5 to stylize and burn your DVD creation iMovie HD & iDVD 5: The Missing Manual.